Interdependence of stock markets: evidence from Vietnam - Tran Thi Van Anh; Dao Hoang Tuan; Nguyen Thi Nhung (Journal of International Economics and Management, 2022)
The study investigates the effect of spillovers regionally and worldwide on Vietnam’s stock market. The vector error correction model (VECM) is used to analyze the collected data from Bloomberg. Data include eight comparable stock market indices, namely DJI, NKY, SHCOMP, SET, MXSG, PCOMP, FBMKLCI, and JCI. The empirical results show that the Vietnamese stock market is significantly linked to that of the other countries. During the periods of dramatic market fluctuation, the cross-border linkage between the VN-Index and comparable indices is the largest. The impact of the stock markets of small nearby countries such as Singapore and Malaysia on the Vietnamese stock market are greater than the other large ones including the United States, Japan and China. The findings of this study contribute to the literature on the interdependence and interaction of stock markets. The common economic integration, especially in showing that effect found in other studies, is meaningful in explaining the observed phenomenon.